Students' Perception of YouTube Music as a Learning Media for Listening Mastery in Senior High School: Rheinata Aprilliana*, Pipit Novita - Rheinata Aprilliana; Pipit Novita (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
Research on students' perceptions of YouTube music as a learning medium is very important to carry out considering that learning media is currently an important instrument in education. This research aims to explore students' perceptions of YouTube Music as a learning medium for listening mastery at the high school level, both related to student motivation and the impact of YouTube Music. The research methodology used in this research is descriptive quantitative and data was collected using a questionnaire with 18 statement items related to YouTube Music. Research findings show that there are positive student perceptions of the use of YouTube Music in improving listening skills. Firstly, YouTube Music motivates students to master listening because YouTube can attract their attention, increase their motivation, and increase their interest in learning. Secondly, most students have a perception positive of YouTube Music, it can be seen that students stated that YouTube Music has many benefits as a learning media to improve listening. Thirdly, based on their perceptions, YouTube Music improves students' listening abilities by increasing students' vocabulary knowledge. The students also agree that YouTube music is used as a listening medium in class. Nevertheless, based on this research, several limitations can be considered for future researchers to perfect research because this research has shortcomings that need to be corrected